Steady-state an dynamic solutions of asynchronous links based on variable frequency transformers - Contreras Aguilar, Luis Alberto (Universidad Michoacana de San Nicolás de Hidalgo, 2011)
This thesis presents research carried-out on the modelling and analysis of asynchronous links of electric power systems using Variable Frequency Transformers (VFTs). A procedure to determine the stability of a steady-state solution has been implemented and tested with a VFT model suitable for stability studies. In addition, VFT models for harmonic-oriented and planning studies have been implemented. The aim of the procedure implemented in this work is to determine the stability of a steady-state solution based on a sequential continuation scheme, eigenvalues analysis and a Newton method. The continuation scheme relies on an efficient predictorcorrector scheme, where the correction is accomplished through a Newton method. This acceleration procedure relies on the application of a Newton-Raphson method and the Poincaré map. More important, eigenvalues are computed with the transition matrix identified with a Newton method using a Direct Approach or a Numerical Differentiation procedure. In other words, all the information required to implement the stability analysis is provided by the Newton method. Furthermore, a comprehensive VFT park model is proposed to study the stability of asynchronous links. The VFT park allows the simulation of multi-unit VFTs operated in parallel in order to increase the power transfer between two electric power networks. Each VFT unit consists of a wound rotor induction machine, a DC motor and a control system, which provides power transfer regulation using power and speed controllers. Stability diagrams are reported for changes of the VFT parameters, power transfer and frequency on both sides of the asynchronous link. Even though the VFT is operated within its rated power transfer limits, simulation results reveal that a VFT may become unstable not only for changes of power transfer but also for variations of frequency.

Esta tesis presenta el análisis y modelado el dominio del tiempo de enlaces asíncronos de sistemas de potencia asíncronos utilizando Transformadores de Frecuencia Variable (por sus siglas en inglés, VFTs). El análisis se realiza por medio de estudios de estabilidad, análisis de armónicos y estudios de planeación. En esta tesis se implementa un procedimiento para determinar la estabilidad de la solución de estado estable basado sobre un esquema de continuación secuencial, análisis de valores característicos y un método Newton. El esquema de continuación se basa en un eficiente esquema predictor-corrector en donde el corrector se implementa con un método Newton. Este procedimiento de aceleración se basa en la aplicación del método de Newton-Raphson y el mapa de Poincaré. Aún más importante, los valores característicos se calculan con la matriz de transición identificada con un método Newton usando un procedimiento de Aproximación Directa o Diferenciación Numérica. Es decir, toda la información requerida para implementar el análisis de estabilidad la provee el método Newton. Por otra parte, se propone un modelo completo del parque de VFTs para estudiar la estabilidad de enlaces asíncronos. El parque de VFTs permite la simulación de múltiples unidades operando en paralelo de forma coordinada con la finalidad de incrementar la transferencia de potencia entre los sistemas enlazados. Cada unidad consiste de una máquina de inducción de rotor devanado, un motor de corriente continua y su sistema de control, el cual proporciona regulación de transferencia de potencia utilizando reguladores de potencia y velocidad. Se reportan diagramas de estabilidad para cambios en los parámetros de transferencia de potencia en el VFT y frecuencia en ambos lados del enlace.
Facultad de Ingeniería Eléctrica. Doctorado en Ciencias en Ingeniería Eléctrica
Keywords: info:eu-repo/classification/cti/7; FIE-D-2011-0019; VFT; Estabilidad; Método Newton; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3336